Pengaruh Keterampilan Komunikasi Mahasiswa terhadap Keberhasilan Melaksanakan Program Pejuang Muda Kementerian Sosial: - Devira Nur Astria; Chendi Liana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study uses a quantitative approach with a simple linear regression analysis method. The theory used is the Communication Accommodation Theory from Howard Giles, which explains how and why a person adapts his communication behavior to the actions of others. The results of this study are (1) the average value of student communication skills is 65 with a percentage of 41% which is in the "Very High" category. (2) the average score of success in implementing Young Fighters program of the Ministry of Social is 84.6 with a percentage of 34% being in the "High" category. (3) there is a positive and significant influence between student communication skills on the success of implementing Young Fighters program of the Ministry of Social. It is proven from the results of a simple linear regression test showing a significance value of 0.000 < 0.05 then Ha is accepted. The correlation coefficient of 0.746 indicates the relationship between variables in the "Strong" category is positive. The magnitude of the influence of student communication skills on the success of implementing Young Fighters program of the Ministry of Social is 55.6%. While the remaining 44.4% is influenced by factors other than those studied. The regression equation Y = 18.225 + 1.026X. The higher the student's communication skills, the higher the success of implementing Young Fighters program of the Ministry of Social. Keywords: Communication Skills, Success, Young Fighters Program.